Global Attractor and Inertial Manifolds for Regeneration of Severed Limb Equation (Journal of Partial Differential Equations, 2020)
In this paper the existence of the compact global attractor and inertial manifolds for regeneration of severed limb equation are proved.
Keywords: Global attractor; inertial manifold; nonlinear evolutionary equation